Scratch Collapse Test Is a Useful Clinical Sign in Assessing Long Thoracic Nerve Entrapment - Pinder, Elizabeth M.; Ng, Chye Yew (Journal of Hand and Microsurgery, 2016)
The scratch collapse test (SCT) is a relatively new clinical test in which a positive result implies entrapment neuropathy of the nerve tested. Initially described for carpal and cubital tunnel syndromes, subsequent authors have found it useful for the assessment of median, ulna, radial, axillary, and common peroneal nerves. We report a case illustrating the value of the SCT in the clinical assessment of thoracic nerve entrapment.
Keywords: long thoracic nerve; long thoracic nerve palsy; nerve entrapment; scapula winging; scratch collapse test